TEACHER INNOVATIVE WORK BEHAVIOR IN TAHFIDZ ISLAMIC BOARDING SCHOOLS: THE ROLE OF SELF-EFFICACY, TRANSFORMATIONAL LEADERSHIP, AND ORGANIZATIONAL SUPPORT - Lina Novita; Rohimah Rohimah; Elly Sukmanasa; Hasan Baharun (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
Innovative Work Behaviour (IWB) is increasingly required for teachers in responding to educational transformation. However, empirical evidence from faith-based boarding schools remains limited. This study aims to analyse the combined influence of self-efficacy, transformational leadership, and organizational support on teachers’ innovative work behaviour in tahfidz-based Islamic boarding schools in Indonesia. A quantitative correlational design was employed involving 159 teachers selected through proportionate random sampling. Data were collected using validated Likert-scale instruments and analysed using Pearson correlation and multiple regression. The results indicate that self-efficacy (β = 0.298, p < .001), transformational leadership (β = 0.355, p < .001), and organizational support (β = 0.332, p < .001) significantly influence innovative work behaviour. These variables explain 83.2% of the variance in IWB (R² = .832), with transformational leadership as the strongest predictor. This study contributes theoretically by extending innovation behaviour models into faith-based educational settings, highlighting the dominant role of leadership in structured and value-based institutions.